A grammar of Bilinarra an Australian aboriginal language of the Northern Territory - Meakins, Felicity (Pacific linguistics, 2014)
This volume provides the first comprehensive description of Bilinarra, a Pama-Nyungan language of the Victoria River District of the Northern Territory (Australia). Bilinarra is a highly endangered language with only one speaker remaining in 2012 and no child learners. The materials on which this grammatical description is based were collected by the authors over a 20 year period from the last first-language speakers of the language, most of whom have since passed away. Bilinarra is a member of the Ngumpin subgroup of Pama-Nyungan which forms a part of the Ngumpin-Yapa family, which also includes Warlpiri. It is non-configurational, with nominals commonly omitted, arguments cross-referenced by pronominal clitics and word order grammatically free and largely determined by information structure. In this grammatical description much attention is paid to its morphosyntax, including case morphology, the pronominal clitic system and complex predicates. A particular strength of the volume is the provision of sound files for example sentences, allowing the reader access to the language itself